Learning Activities of Indonesian Language Content Using The Project Based Learning Model - Rossy Arlinda; Iriani Bakti; Norestawati Norestawati (FKIP ULM, 2023)
The purpose of this study was to determine teacher and student activities as well as to improve student learning outcomes. This research used Classroom Action Research (CAR). This research was conducted in two cycles. This research was conducted in class IV-A of SDN Melayu 2 with 22 students. The data were analyzed qualitatively, namely teacher and student activities, and quantitatively, namely student learning outcomes. The data generated from the instrument sheet, observation sheets and learning outcomes tests were then analyzed using descriptive techniques and described in the form of tables and graphs, then students understood using the criteria for each indicator of the achievement of teacher activities and activities, as well as the achievement of mastery learning and individually classic. The study's findings showed that the teacher's activity in cycle 1 obtained a score of 19